Role of inhaled corticosteroids in the exacerbation rate of moderate chronic obstructive pulmonary disease - Maida Rakanović-Todić; Sanita Maleškić; Lejla Burnazović Ristić; Aida Kulo Ćesić; Jasna Kusturica; Besim Prnjavorac (Medicinski glasnik, 2017)
Aim: To analyse frequency of chronic obstructive pulmonary disease (COPD) exacerbation in patients on therapy with inhaled corticosteroids (ICS) and relevant factors that influence the rate of COPD exacerbations in a subgroup of moderate illness, like FEV1, comorbidities and other concomitant therapy. Methods: The study included patients with moderate COPD with at least 10 pack-years history of smoking and accompanying cardiovascular comorbidity. Demographic data, frequency of exacerbations and information about proscribed treatments-ICS alone or in combination with long acting beta agonist (LABA), were collected from medical records for the previous 12 months from the index date. Results: Data were collected for 210 patients (170 males) with the mean age 65.63±8.66 years, 72 of which were treated with a fixed combination of long acting beta blocker (LABA) and ICS. Significantly more frequent exacerbations were detected in patients using ICS p<0.0001) and having higher Modified British Medical Research Council (mMRC) score p=0.004). No statistically significant difference was registered related to ratio of FEV 1 /FVC (p=0.121) or a number of cardiovascular comorbidities per patient (p=0.969). Conclusions: Our results present a small contribution to the current scientific discussion about the use of ICS in COPD treatment. Further prospective studies are needed to confirm the impact of ICS on the frequency of COPD exacerbations.
Keywords: chronic obstructive pulmonary disease; inhaled corticosteroids; exacerbations